Gross Anatomy of the Spinal Cord: An Online Learning Module - Rae Russell; Lisa Lee (Association of American Medical Colleges, 2014)
Abstract "Gross Anatomy of the Spinal Cord: An Online Learning Module" is a concise yet high-yield introductory tutorial or review on spinal cord anatomy. The narrated lecture presentation and accompanying lecture slides are intended primarily for medical, dental, and allied health students who wish to efficiently learn the anatomy of the spinal cord. Further, the presentation may be useful for undergraduate anatomy teachers and students who may be considering careers in health sciences but do not have access to cadaveric specimen or images. This presentation integrates spinal cord neuroanatomy and gross anatomy with protective structures that surround the spinal cord. The module contains original images of spinal cord anatomy acquired through a special dissection approach to display structures that are not easily seen through typical dissections. The original diagrams feature a simplified approach to master the concept of spinal and nerve pathways that are typically considered confusing to teach, as well as to learn. The module leads the user on an introductory tour through spinal cord anatomy in a way no other available online resource has yet to date. The content of the learning module was validated by anatomy faculty members, and its educational value was pilot tested with a small sample of the first year physical therapy students enrolled in a gross anatomy course during summer 2013. Pre- and postlearning module quizzes were administered to test effectiveness of the module as an educational resource. A survey was also conducted to evaluate students' perceived value of the module and to solicit suggestions for improvements to enhance the module's efficiency. The results of this deployment revealed that learning does occur after engaging in the online module. The survey results revealed that a majority of students found the module to be both useful and highly valuable. Overall, the online learning module was found to be a useful supplementary source for preview of in-class learning or for review.